Strategies For Internalizing PAI Values In Learning At Majelis Taklim - Yustina Yuliasari (At-Tarbiyat, 2023)
Islamic Religious Education (PAI) has an important role in shaping the character and morals of individuals, especially in the Taklim Assembly environment, which is often a place to learn Islamic religion and culture. The internalization of PAI values in learning at Majelis Taklim has a significant impact on learners' personal and social development. This study aims to identify strategies for internalizing PAI values in learning at Majelis Taklim. The data in this study were obtained from a literature study to understand the theoretical basis of Islamic Religious Education, the internalization strategy of PAI values, and Majelis Taklim. Primary and secondary data were obtained from research papers that have been published in national and international journals with high credibility from Sinta 5 to Scopus. Data analysis in this study goes through several processes, first collecting data obtained both from interviews, and documentation, after which the data is grouped according to its type, then describing it into units, synthesizing, compiling into patterns, and ending with making true conclusions. The results of this study indicate that the strategy of internalizing PAI values in learning at Majelis Taklim involves interaction between teachers, curriculum, social interaction, and technology. By integrating these factors, Majelis Taklim can be an effective environment to internalize PAI values in the lives of learners. Thus, this study can serve as a guide for the development of PAI learning programs in Majelis Taklim and similar educational institutions.